The Influence of Typical Versus Atypical Ads On Sharing Intention - Rita, Paulo (2022)
Rita, P., Guerreiro, J., & Matos, S. (2022). The Influence of Typical Versus Atypical Ads On Sharing Intention. International Journal of Internet Marketing and Advertising. https://doi.org/10.1504/IJIMA.2023.10050